Multisystemic Inflammatory Syndrome in Children From the South of Colombia: One Year of Experience - Pérez López, Pilar; Carvajal Duque, Darling; Salgado García, Doris Martha; Vega Vega, Martha Rocío; Ramos-Castaneda, Jorge Andrés; Ardila Gómez, Iván José; Romero, Andrés Felipe (Frontiers in Pediatrics, 2022)
Background: multisystemic Inflammatory Syndrome in children (MIS-C) is one of the most severe presentations of COVID-19 infection in pediatrics. Currently we have few studies that describe the characteristics of this condition in Colombian children. Objective: to describe the clinical and epidemiological characteristics of children hospitalized with MIS-C in Neiva, Colombia. Methods: observational follow-up study of a cohort of children with MIS-C for 12 months (May 15, 2020 to May 30, 2021) in two hospitals in the city of Neiva. Epidemiological data, clinical characteristics, laboratory characteristics, cardiological evaluation, treatment and clinical outcomes were analyzed. Results: We included 34 patients who met the diagnosis of MIS-C. The median age was 68 months. Some type of nutritional issue was observed by 43.75% of those under 5 years of age and by 27.78% of those over 5 years of age. Gastrointestinal symptoms were the most frequent, being vomiting, diarrhea and abdominal pain the most frequent by 79%, 70%, 67% respectively. By 77% of the patients, a history of SARS-COV-2 infection was documented through IgG. In the echocardiogram, 35.4% of the patients had systolic dysfunction, followed by coronary involvement by 35%. Conclusions: this study describes a series of cases of children with MIS-C in Colombia. Gastrointestinal manifestations were predominant. Mortality was high in comparison to other countries but similar to that reported in Colombia. This was associated with relevant pathological background. More training is required for physicians to have a better understanding of the disease so as to have an early diagnosis and timely treatment